Low‐temperature sintering of CaMgSi2O6-KBS composites with ultralow dielectric constant. Issue 11 (1st August 2020) - Liu, Dongshuo; Zhong, Chaowei; Qin, Tianying; Yang, Qiu; Tang, Bin; Zhang, Shuren
Abstract: In this paper, ultralow dielectric constant CaMgSi2 O6 -KBS composites ( ε r  < 5) were fabricated via the solid-state route. The sintering temperature ( ST ) of CaMgSi2 O6 ceramics was successfully reduced from more than 1200 °C–850 °C with assistance of the K2 O–B2 O3 –SiO2 (KBS) glass. The impacts of KBS glass on phase compositions, microstructure, sintering activation energy and microwave dielectric properties of CaMgSi2 O6 ceramics were systematically discussed. The X-ray diffraction results confirmed that the (1- x )CaMgSi2 O6 - x KBS composites possessed CaMgSi2 O6 phase and SiO2 phase. The results of Rietveld refinement showed that the weight fraction of CaMgSi2 O6 phase gradually decreased with increasing KBS glass and sintering temperature. The (1- x )CaMgSi2 O6 - x KBS ( x  = 0.5) composite sintered at 850 °C exhibits optimal microwave dielectric properties: ε r  = 4.58, Q × f  = 13989 GHz (13.95 GHz), τ f  = -22.9 ppm/ o C. It is a promising material for low-temperature co-fired ceramic (LTCC) applications which desire for ultralow dielectric constant materials.